(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The aim of this research is to try to shed light on the effectiveness of the work of banks when approving mergers between them, to identify the extent to which the banking system benefits from banking mergers, as it is one of the important means of raising the effectiveness of the banks’ performance and increasing their financial capabilities as a step to encourage banks to merge with each other. Banking merger has repercussions on the performance of the banking sector in improving the level of profitability and banking liquidity. The research relied on the deductive approach by monitoring and studying some international experiences, (evaluating the experience of the merger of First Gulf Bank with SABB Bank, and financial data were taken two years before the merger and four years after the merger) and (evaluating the experience of the merger of First Gulf Bank and National Abu Dhabi, and financial data were taken. Two years before the merger and four years after the merger) and he also used the quantitative method by using financial indicators to reach the results of evaluating these experiences. The research reached a set of conclusions, the most important of which is that the merger had positive repercussions on the banking performance of liquidity indicators, while it had a negative impact on profitability indicators. There is a noticeable increase in the customer base and an increase in banking capital